1994
DOI: 10.1207/s15327752jpa6303_12
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of MMPI-168 Code Types Among Asymptomatic and Symptomatic HIV-1 Seropositive Gay Men

Abstract: Welsh codes of Minnesota Multiphasic Personality Inventory-168 (MMPI-168) profiles were calculated for 151 HIV-1 seropositive gay men and 27 gay seronegative controls. Although 99% of seropositives' profiles were clinically elevated, the profile configurations among subjects were varied. These data document the presence of considerable emotional distress among HIV-infected individuals, yet the heterogeneity of codes encountered argues against generalizations of seropositive subjects based upon mean MMPI profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…Specifically, differences on the Hs, D, Pd, Mf, Pt, and Sc Scales between groups were found in this study. These findings are consistent with the results of prior studies of distress and clinical symptoms on the MMPI that have found that HIV+ patients reported greater amounts of depression, somatic complaints, and anxiety, as well as elevations on the Pd, Mf, and Sc Scales (Hestad et al, 1994;Moore et al, 1994;Pakesch et al, 1992). However, in the present study, when the analyses were controlled for demographic differences, the differences on these scales appeared to be due to disparities in race and gender distribution in the groups rather than the presence of HIV-1.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, differences on the Hs, D, Pd, Mf, Pt, and Sc Scales between groups were found in this study. These findings are consistent with the results of prior studies of distress and clinical symptoms on the MMPI that have found that HIV+ patients reported greater amounts of depression, somatic complaints, and anxiety, as well as elevations on the Pd, Mf, and Sc Scales (Hestad et al, 1994;Moore et al, 1994;Pakesch et al, 1992). However, in the present study, when the analyses were controlled for demographic differences, the differences on these scales appeared to be due to disparities in race and gender distribution in the groups rather than the presence of HIV-1.…”
Section: Discussionsupporting
confidence: 91%
“…Correspondence concerning this article should be sent to Kevin R. Robertson, Ph.D., AIDS Neurological Center, Neurology, 751 Clinical Sciences Building, Campus Box #7025, University of North Carolina at Chapel Hill, School of Medicine, Chapel Hill, NC 27599-7025;phone: 919-966-5549;fax: 919-966-2922;e-mail: kevinr@ glial.med.unc.edu. Several studies have used the Minnesota Multiphasic Personality Inventory (MMPI) or a shortened variation to assess patterns of psychological distress in HIV+ individuals, primarily in homosexual males or intravenous drug users (IVDUs). Consistent with previous research findings indicating HIV+ individuals experience increased symptoms of psychological distress (e.g., Atkinson et al, 1988;Catalan et al, 1992), studies comparing the MMPI scores of HIV+ and HIV-homosexual males have shown HIV+ males to have elevated MMPI scores, primarily on the Depression (D) Scale (Drebing et al, 1994;Kovner et al, 1989;Moore, van Gorp, Hinkin, Holston, & Weisman, 1994).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Several researchers have looked at the prevalence of psychiatric morbidity and found it to be higher in HIV-positive (Brown et al, 1992;McDaniel et al, 1995;Moore et al, 1994). Others have found psychiatric morbidity to be related to symptoms of HIV disease only (Kalichman et al, 1995;Fell et al, 1993) and some have found no evidence for a higher prevalence (Pergami et al, 1994;Rabkin et al, 1990).…”
Section: Introductionmentioning
confidence: 99%